High charge carrier mobility in two dimensional indium (iii) isophthalic acid based frameworks - Panda, Tamas; Banerjee, Rahul (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2014)
The effect of dimensionality (1D to 2D) on charge carrier mobility have been studied thoroughly on three In(III)-isophthalate based MOFs [In-IA-1D, In-IA-2D-1 and -2]. In-IA-1D possess 1D nanotubular architecture with [(CH3)(2)NH2](+). In-IA-2D-1 have 2D layers containing only [(CH3)(2)NH2](+) cations. Whereas, In-IA-2D-2 have [(CH3)(2)NH2](+) cations as well as solvent DMF molecule inside the crystal structure. Due to presence of the pi-pi stacking arrangement among the phenyl rings of IA moieties facilitates the high charge carrier mobility (4.6 x 10(-3) cm(2) V-1 s(-1) at V-G = -40 V) in In-IA-2D-2. However, In-IA-1D and In-IA-2D-1 does not show any charge carrier mobility due to absence of pi-pi stacking arrangement.
Keywords: Charge carrier mobility; Coordination chemistry; metal organic framework; pi-pi stacking